Developing and Selecting A Strategy for Interaction with Stakeholders During the Project Life Cycle in Oil Projects - Raman Rezaei (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aimed to develop and select a strategy for interacting with stakeholders during the life cycle of oil projects using the SWOT matrix, the fuzzy TOPSIS method, and a proposed mathematical model in Pars Oil and Gas Company. Methodology: For this purpose, 9 strengths, 8 weaknesses, 7 threats, and 8 opportunities were presented, and then 15 proposed strategies using the views of a sample of 23 people available from experts in the studied projects. Then, strategies were ranked using the fuzzy TOPSIS method in Excel. In the last step, the proposed mathematical model was solved using Gamz software, and the interaction strategy with stakeholders was determined. Findings: Findings showed that the numerical value of internal factors was 0.124, and the numerical value of external factors was 0.003. Therefore, the company's strategic position was in the first area, and it was necessary to put aggressive strategies on the agenda of this company. Also, the ranking of strategies was done using the fuzzy TOPSIS method, and the findings of solving the mathematical model to select the optimal strategy of interaction with stakeholders showed that the results of the mathematical model are different from the result of multi-criteria decision-making and each strategy can relate to several conflicts Improve stakeholders. Originality/Value: This article adds scientific value by providing a way to identify, prioritize, and determine appropriate strategies for interacting with stakeholders.